HyMaTZ: A Python Program for Modeling Seismic Velocities in Hydrous Regions of the Mantle Transition Zone. (4th August 2018) - Wang, Fei; Barklage, Mitchell; Lou, Xiaoting; van der Lee, Suzan; Bina, Craig R.; Jacobsen, Steven D.
Abstract: Mapping the spatial distribution of water in the mantle transition zone (MTZ, 410‐ to 660‐km depth) may be approached by combining thermodynamic and experimental mineral physics data with regional studies of seismic velocity and seismic discontinuity structure. HyMaTZ (Hydrous Mantle Transition Zone) is a Python program with graphical user interface, which calculates and displays seismic velocities for different scenarios of hydration in the MTZ for comparison to global or regional seismic‐velocity models. The influence of water is applied through a regression to experimental data on how H2 O influences the thermoelastic properties of (Mg, Fe)2 SiO4 polymorphs: olivine, wadsleyite, and ringwoodite. Adiabatic temperature profiles are internally consistent with dry phase proportion models; however, modeling hydration in HyMaTZ affects only velocities and not phase proportions or discontinuity structure. For wadsleyite, adding 1.65 wt% H2 O or increasing the iron content by 7 mol% leads to roughly equivalent reductions in V S as raising the temperature by 160 K with a pyrolite model in the upper part of the MTZ. The eastern U.S. low‐velocity anomaly, which has been interpreted as the result of dehydration of the Farallon slab in the top of the lower mantle, is consistent with hydration of wadsleyite to about 20% of its water storage capacity in the upper MTZ. Velocity gradients with depth in absolute shear velocity models are steeper in all seismic models than all mineralogical models, suggesting that the seismic velocity gradients should be lowered or varied with depth and/or an alternative compositional model is required. Plain Language Summary: Olivine and its high‐pressure polymorphs, wadsleyite and ringwoodite, constitute at least half of the material in the Earth's upper mantle. In addition to magnesium, iron, silicon, and oxygen, these phases are known for their ability to incorporate H2 O. Water is incorporated into their crystal structures as OH (hydroxyl) defects, charge‐balanced primarily by cation vacancies. Hydration of olivine, wadsleyite, and ringwoodite through such defects modifies their density and elastic properties such as the bulk ( K ) and shear ( G ) moduli, which can lead to changes in seismic velocities as determined from analyses of seismograms using methods such as seismic tomography. This paper presents a tool for researchers to calculate and graph the influence of hydration in olivine, wadsleyite, and ringwoodite for comparison to any seismic‐velocity model. While Hydrous Mantle Transition Zone accounts for elastic property changes due to hydration, the effect of water on thermodynamic phase proportions is not yet included. The goal of such studies is to assess the amount and regional distribution of water in the mantle transition zone. Key Points: HyMaTZ calculates seismic velocity profiles for different states of hydration in the transition zone In the upper MTZ, adding 1.65 wt% H2 O, 7 mol% Fe, or increasing temperature by 160 K cause roughly equivalent reductions in V S Velocities within the eastern U.S. low‐velocity anomaly are consistent with ~1 wt% H2 O in wadsleyite along a 1600 K adiabat